Adaptation of NCS report 24 for flattening filter free VMAT quality assurance. (August 2018) - Gillespie, Sean; Casey, Terence; Monnelly, Patrick
Abstract : Volumetric Arc radiotherapy (VMAT) was introduced nearly 10 years ago and is an advancement on the technology of Intensity-Modulated Radiotherapy (IMRT). The main difference between VMAT & IMRT are the increased number of degrees of freedom during patient treatment including gantry rotation, dose rate variation, multi-leaf collimator (MLC) movement and in some cases collimator movement 1 . Because of the aforementioned differences between IMRT and VMAT, the established IMRT Quality Assurance (QA) procedures alone are not sufficient for VMAT QA. To address this shortfall, in 2015 the Nederlandse Commissie voor Stralingsdosimetrie (NCS) published report 24 which is the first fully comprehensive guide of its kind aimed explicitly at VMAT QA and therefore has the potential to be utilised to improve the quality assurance of VMAT. The aim of this work was to integrate machine QA aspects of NCS report 24 as part of Galway Clinic's VMAT QA process & furthermore investigate if this can be adapted to flattening filter free (FFF) beams. QA tests outlined by NCS 24 were performed on an Elekta Versa HD linac. The methods, equipment required to conduct the test set out by NCS 24 was investigated. Analysis of the test results was performed to the standards set by NCS 24 and compared to the standards of TG 142, which is the standard currently employed by the Galway Clinic. The tests set out by NCS 24 were also translated to FFF beam energies using additional sources of information.